IMPLEMENTASI PROGRAM BANTUAN LANGSUNG TUNAI : DESA PANGKALAN LIBUT KECAMATAN PINGGIR KABUPATEN BENGKALIS 2021 - Yoga Lowinski; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Implementation of the direct cash assistance program in Pangkalan Libut Village, namely implementing the direct cash assistance program in Pangkalan Libut Village. From this implementation, Pangkalan Libut Village can reduce the poverty rate in Pangkalan Libut Village . This research aims to determine the implementation of the Direct Cash Assistance (BLT) program in Pangkalan Libut Village, Bengkalis Regency in 2021. The method used in this research is a descriptive method with a mix method type of research. The types of research data are primary data and secondary data. The data analysis technique used is qualitative and quantitative descriptive data analysis. The results of this research are that the implementation of the Direct Cash Assistance (BLT) program in Pangkalan Libut Village, Bengkalis district in 2021 has not gone well, although there are still many obstacles both from within and from outside the implementer. Such as differences in data collection, determining criteria, and competition for aid funds. In terms of communication, the village government has not been effective in distributing direct cash assistance (BLT), secondly, the clarity of socialization has been even, while thirdly, consistency has been good. Disposition/attitude is not good enough for the people who receive assistance. Resources consist of human resources that are quite good in the direct cash assistance program, facilities and infrastructure are adequate for the distribution of BLT. One of the obstacles that occurs is caused by differences in criteria for aid recipients which causes people to compete to get aid, inadequate internet networks, and differences in central and field data. The bureaucracy as the implementer of a program must be able to support programs that have been decided politically by carrying out good coordination. The lack of coordination and cooperation between stakeholders results in program implementation that occasionally experiences problems and improves them well. Keywords: Supervision, Work Discipline, Communication, Employee Performance.